Using Visualisation to Enhance Intermediate EFL Learners' Narrative Writing - Yong Yi (Cranmore Publishing, 2020)
Studies show that visualisation while reading has a positive impact on both L1 and L2 reader's comprehension of a text and that visualisation improves L1 learners' writing, but there are no studies relating to whether visualisation may help L2 learners' writing. Using visualisation as a learning strategy, this paper reports on how visualisation training might affect a group of Chinese intermediate EFL learners' narrative writing. Quantitative data from the pre-test and post-test did not show statistical significance, but the analysis of the qualitative data from learners' written reflections indicated a positive correlation between the use of visualisation and engagement with narrative writing and higher levels of classroom enthusiasm and participation. This study highlights the need for further work to differentiate the most effective aspects of visualisation training for enhancing the quality of narrative writing. It also suggests potential for the integration of visualisation into different writing development curricula and to promote the role of visualisation in the wider process of second or foreign language learning.